Thermal analysis and non‐isothermal kinetics of poly(ethylene glycol) with different molecular weight. Issue 12 (13th January 2014) - Wei, Ting; Zheng, Baicun; Yi, Hongling; Gao, Yanfeng; Guo, Weihong
<x xml:space="preserve">Abstract</x> This study focuses on comprehensively investigating polyethylene glycol (PEG) with different molecular weight. Thermal properties of the PEGs were investigated by differential scanning calorimetry (DSC), as well as gradual melting and freezing tests with thermocouples. Results show that the degree of PEG crystallization increased with the increasing of the molecular weight of polymers. The temperatures of pure PEG 1000 and PEG 1000‐PEG 600 blends ranged from 20 to 50°C. The apparent activation energy of pure PEG1000 was 300 kJ/mol, whereas that of the PEG blend was 239 kJ/mol. During the crystallization process, Avrami index n ranged from 5 to 3 and half‐crystallization time t1/2 decreased with the acceleration of the crystallization rate R. This difference was due to the increase in polydispersity of the PEG system and decrease in the degree of crystallization. POLYM. ENG. SCI., 54:2872–2876, 2014. © 2014 Society of Plastics Engineers